PENGARUH RASIO PREKURSOR : AKTIVATOR TERHADAP KUAT TEKAN MORTAR GEOPOLIMER ABU SEKAM PADI - Ria Dwi Fransiska; Tarmizi (JURNAL ILMIAH BERING'S, 2019)
Production cements portland resulting CO 2 that cause global instillation and a lot of chaff ash waste paddy causes environment sacrilege at territorial kibbling. Therefore developed significant alternative supplementary cement as geopolimer's mortar rice husk ash. This research did by eksprimen's method test-driving at Civil Tech laboratory STT Pagar Alam. Research is with intent to know prekursor's compare influence activator to heavy duty press, firmly presses maximum that at takings while old 28 days. Ratio that utilized by TR 1 1:1 firmly presses as big as 11,33 mpa, TR 2 1:0,85 strength press 10,56 mpa and TR 3 1:0,75 firmly press as big as 8,4 mpa. So gets to be concluded that gets its aged crescent mortar get to regard press strength. The greater ratio which utilized by press strength gets to increase, progressively little ratio which utilized by press strength gets is down.